2011
DOI: 10.5099/aj110300191
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Behavior of Bilirubin Based on [bmim][PF6] As the Supporting Electrolyte in Organic Solvent and Its Analytical Application

Abstract: The electrochemical oxidation behaviors of bilirubin (BR) at the bare glassy carbon electrode (GCE) were studied in dimethyl formamide (DMF) containing 1 vol.% of 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]) as the supporting electrolyte. Some electrochemical parameters of BR oxidation were investigated by cyclic voltammetry and chronocoulometry. The oxidation products were identified by the spectrophotometric technique. The basic BR showed good linear relationship in the range of 2.6×10 -5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The electrocatalytic oxidation of BR and the following oxidation reactions are irreversible by nature as described in Equations (2)–(4) under our experimental conditions, which matches well with earlier reports [ 24 , 37 ]. …”
Section: Discussionsupporting
confidence: 92%
“…The electrocatalytic oxidation of BR and the following oxidation reactions are irreversible by nature as described in Equations (2)–(4) under our experimental conditions, which matches well with earlier reports [ 24 , 37 ]. …”
Section: Discussionsupporting
confidence: 92%
“…The third process occurs at higher potentials and only with MWCNT film-based SPEs. All these oxidation processes were found to be irreversible under our experimental conditions, as some authors have already shown [16,19]. Peaks I and II are attributed to the oxidation of BR and of BV, respectively (Reactions 1 and 2).…”
Section: Cyclic Voltammetry With Bare and Nanostructured Spesmentioning
confidence: 66%
“…Therefore, the electrochemistry of BR has been investigated in detergents such as Tris Buffer [13,16] or in organic solvents such as dimethyl sulfoxide (DMSO) [17], dimethyl formaldehyde [18] and room temperature ionic liquids [19]. To simulate the physiological environment, some authors have also investigated the …”
Section: Introductionmentioning
confidence: 99%
“…During the electrolytic oxidation of BR in dimethyl sulfoxide and dimethyl formamide , the formation of various tetrapyrrolic derivatives was recorded. The reaction rate generally increases with increasing of solvent polarity .…”
Section: Introductionmentioning
confidence: 96%